Traditional Beliefs and Practices among post-partum women attending Postpartum clinic, at Bukulula Health Centre IV Kalungu district (Student's Journal of Health Research Africa, 2021)
Background:Maternal deaths in the postpartum period contribute greatly to the global burden of maternal mortality especially in developing countries where 99% of these maternal deaths occur. Almost 40% of women develop serious illness after birth, and close to 50% of maternal deaths occur after delivery. Other problems encountered during the postpartum period include anemia, nutritional deficiencies, infection, family violence, and emotional problems most of which are associated with the mothers’ traditional beliefs and practices. Some of these beliefs and practices used are beneficial to their health, some are non-beneficial but harmless whereas others are harmful and greatly contribute to maternal morbidity and mortality.Methodology: This was a qualitative descriptive study that was conducted among ten purposively selected postpartum women attending a postpartum clinic at Bukulula health center IV. Data was collected through in-depth face-to-face interviews using a semi-structured interview guide and an audio recorder to track the proceedings of each interview. Data were analyzed based on emerging themes, following transcription of the interviews.Results:Three themes emerged from the study and these were; dietary precautions, behavioral precautions and hygiene, and physical warmth.Conclusion and recommendation: Some of the traditional beliefs and practices held by postpartum women are beneficial and can be incorporated into routine care provided whereas others are harmful and need to be restructured.